The miR-23–27–24 cluster: an emerging target in NAFLD pathogenesis - Ru Lin; Wang Xiao-mei; Niu Jun-qi (Acta Pharmacologica Sinica, 2022)
The incidence of non-alcoholic fatty liver disease (NAFLD) is increasing globally, being the most widespread form of chronic liver disease in the west. NAFLD includes a variety of disease states, the mildest being non-alcoholic fatty liver that gradually progresses to non-alcoholic steatohepatitis, fibrosis, cirrhosis, and eventually hepatocellular carcinoma. Small non-coding single-stranded microRNAs (miRNAs) regulate gene expression at the miRNA or translational level. Numerous miRNAs have been shown to promote NAFLD pathogenesis and progression through increasing lipid accumulation, oxidative stress, mitochondrial damage, and inflammation. The miR-23–27–24 clusters, composed of miR-23a–27a–24–2 and miR-23b–27b–24–1, have been implicated in various biological processes as well as many diseases. Herein, we review the current knowledge on miR-27, miR-24, and miR-23 in NAFLD pathogenesis and discuss their potential significance in NAFLD diagnosis and therapy.